2012
DOI: 10.1111/j.1751-7915.2012.00364.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community structure and dynamics in anaerobic fluidized‐bed and granular sludge‐bed reactors: influence of operational temperature and reactor configuration

Abstract: SummaryMethanogenic community structure and dynamics were investigated in two different, replicated anaerobic wastewater treatment reactor configurations [inverted fluidized bed (IFB) and expanded granular sludge bed (EGSB)] treating synthetic dairy wastewater, during operating temperature transitions from 37°C to 25°C, and from 25°C to 15°C, over a 430‐day trial. Non‐metric multidimensional scaling (NMS) and moving‐window analyses, based on quantitative real‐time PCR data, along with denaturing gradient gel e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 59 publications
5
23
0
Order By: Relevance
“…Hydrogenotrophic genera (>63.7%) made up a large portion of the archaeal community in winter. These findings were in line with the previous observations of methanogen population shifts to favor hydrogen utilization under low temperatures [25,[41][42][43]. It might be explained that lower temperature in winter affected the microbial membrane fluidity and inhibited the utilization of acetate than H 2 [44].…”
Section: Shifts In Microbial Community Structures With Seasonal Tempesupporting
confidence: 92%
“…Hydrogenotrophic genera (>63.7%) made up a large portion of the archaeal community in winter. These findings were in line with the previous observations of methanogen population shifts to favor hydrogen utilization under low temperatures [25,[41][42][43]. It might be explained that lower temperature in winter affected the microbial membrane fluidity and inhibited the utilization of acetate than H 2 [44].…”
Section: Shifts In Microbial Community Structures With Seasonal Tempesupporting
confidence: 92%
“…By 7 February 2011, the percentage of Methanosaeta concilii had decreased to 61% of the clones, while Methanobrevibacter smithii had increased to 39% of the clones. The increase in the abundance of hydrogenotrophic methanogens due to decreasing temperature was also observed by Bialek et al [15].…”
Section: Reduced Biogas Yieldsupporting
confidence: 75%
“…Leven et al (2007) showed that Chloroflexi and Bacteroidetes represented the major phyla at mesophilic temperatures, whilst the phylum Thermotogae was the dominant group in the thermophilic range. In relation to the archaeal community, Methanomicrobiales dominated at 15 • C, and Methanosaeta and Methanomicrobiales were the most abundant at 37 • C (Bialek et al, 2012). Summarizing, these studies confirm the temperature as a parameter affecting the structure of the microbial communities, even more than the increase in the organic loading rate (OLR) (Guo et al, 2014), but they lack transient membership of the microbial community during the days of the temperature perturbation.…”
Section: Introductionmentioning
confidence: 75%